1990
DOI: 10.1016/0735-1097(90)90275-t
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of left ventricular thrombi: Their appearance and resolution in the posthospitalization period of acute myocardial infarction

Abstract: A series of 198 consecutive patients with acute myocardial infarction were prospectively studied before hospital discharge and during 24.0 +/- 8.6 months of follow-up. A predischarge thrombus was found in 38 (31%) of 124 patients with anterior infarction but in none of 74 patients with inferior infarction (p less than 0.001). Early thrombolytic therapy in 34 patients did not decrease the rate of thrombus occurrence. Acute anterior infarction, ejection fraction less than or equal to 35% and apical dyskinesia or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
132
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(137 citation statements)
references
References 54 publications
2
132
0
3
Order By: Relevance
“…In a natural history study of 198 patients admitted for acute MI in the 1980s, LVT developed only in patients with anterior wall MI (1). Stepwise logistic regression analysis identifi ed anterior location of the infarct, decreased left ventricular EF (<35%), and apical dyskinesia or aneurysm as having the highest association with LVT formation during hospitalization (1). Consistent with this, we included only patients with EF ≤35% in our study, which resulted in patients in the study having had an estimated median EF of 31%, with anterior akinesis described in 79% of patients.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…In a natural history study of 198 patients admitted for acute MI in the 1980s, LVT developed only in patients with anterior wall MI (1). Stepwise logistic regression analysis identifi ed anterior location of the infarct, decreased left ventricular EF (<35%), and apical dyskinesia or aneurysm as having the highest association with LVT formation during hospitalization (1). Consistent with this, we included only patients with EF ≤35% in our study, which resulted in patients in the study having had an estimated median EF of 31%, with anterior akinesis described in 79% of patients.…”
Section: Discussionmentioning
confidence: 72%
“…Th e reported incidence of LVT formation and subsequent embolization varies based on the timing of the echocardiographic examination and the diagnostic, anticoagulation, and reperfusion strategies utilized in managing the initial presentation but is noted to range from 0 to as high as 86% (1)(2)(3)(4)(5)(6)(7)(8)(9). Warfarin as a prophylactic strategy is therefore utilized and suggested in guidelines based on data derived from pooled results of studies done before catheter-based treatment of STEMI was prominent (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Regression in size of the thrombus was seen in those treated with anticoagulation. Low levels of symptomatic systemic embolization were seen in this and other studies that demonstrated similar incidence (Visser et al, 1985;Johannessen et al, 1987;Keren et al, 1990). In a review, Cregler (1992) advocated 3 months of warfarin therapy for those with large anterior myocardial infarction or post-infarct heart failure.…”
Section: Comment On Guidelines On Oral Anticoagulation With Warfarin4mentioning
confidence: 95%
“…6,7) Systemic embolism occurred in 4%-63% of patients with a ventricular thrombus documented by echocardiography. 8) We detected a left ventricular thrombus in the apical region on preoperative echocardiography. However, the left ventricular thrombus had disappeared on postoperative echocardiography.…”
Section: Discussionmentioning
confidence: 99%